If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 8y = 9y Solving -6 + 8y = 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. -6 + 8y + -9y = 9y + -9y Combine like terms: 8y + -9y = -1y -6 + -1y = 9y + -9y Combine like terms: 9y + -9y = 0 -6 + -1y = 0 Add '6' to each side of the equation. -6 + 6 + -1y = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1y = 0 + 6 -1y = 0 + 6 Combine like terms: 0 + 6 = 6 -1y = 6 Divide each side by '-1'. y = -6 Simplifying y = -6
| y=x^3+4x^2-5x | | 3x+2=7x-18 | | 9m+12=3m-24 | | 3k=-3k+12 | | 3x+2x=7x-18 | | (7+3x)-(2x+5)=8 | | -4-3k=-3k+8 | | x+5-6=1 | | 31+3y-12=15y-9-5y | | 9n=-2n+35 | | 9(8f-5)+13=12f-2 | | .60p=p-32 | | 6m+8=80 | | 15=4y+x | | 6n-9=51 | | X=20+-4 | | 15=4x+y | | x+17.95=71.80 | | 3r+6*6=3r-1*5 | | 15=y+4x | | 8=8-4(x+1) | | 9k+1=3(3k-1) | | 14-4(w-7)=22 | | 8(x+1)=8 | | 4y+5=15 | | -21+-3= | | e=450-18920 | | ux+vy=wforx | | -2=y-9 | | 11+9j^2=15 | | 38x+36=5(x+2)*7x+4 | | x^3+10x^2-8x-40=0 |